2022
DOI: 10.1007/s13659-022-00350-3
|View full text |Cite
|
Sign up to set email alerts
|

New seco-anthraquinone glucoside from the roots of Rumex crispus

Abstract: A new seco-anthraquinone, crispuside A (1), and three new 3,4-dihydronaphthalen-1(2H)-ones, napthalenones A-C (2–4), were isolated from the roots of Rumex crispus L., along with 10 known anthraquinones (6–14) and naphthalenone (5). Their structures were fully determined by extensive spectroscopic analyses, including ECD, and X-ray crystallography in case of compound 5, whose absolute configuration was determined for the first time. The isolates 1, 6–14 were evaluated for their anti-inflammatory and anti-fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…Flavonoids (flavonols, flavones, isoflavone, chalcones, and anthocyanidin) are the most abundant polyphenols identified in the extract, and several of these compounds are present as Flavonoid Glycosides [ 30 ]. Unlike other reports for the genus Rumex, where the presence of anthranoids is abundant [ 27 , 31 ], in our study, only the compound 3,8-Dihydroxy-1-methylanthraquinone-2-carboxylic acid is identified. Table 1 shows the 25 compounds with the highest relative abundance in the extract.…”
Section: Resultscontrasting
confidence: 89%
“…Flavonoids (flavonols, flavones, isoflavone, chalcones, and anthocyanidin) are the most abundant polyphenols identified in the extract, and several of these compounds are present as Flavonoid Glycosides [ 30 ]. Unlike other reports for the genus Rumex, where the presence of anthranoids is abundant [ 27 , 31 ], in our study, only the compound 3,8-Dihydroxy-1-methylanthraquinone-2-carboxylic acid is identified. Table 1 shows the 25 compounds with the highest relative abundance in the extract.…”
Section: Resultscontrasting
confidence: 89%